2020
DOI: 10.21203/rs.3.rs-23831/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase II Multicenter Randomized Controlled Clinical Trial on the Efficacy of Intra-articular Injection of Autologous Bone Marrow Mesenchymal Stem Cells with Platelet Rich Plasma for the Treatment of Knee Osteoarthritis

Abstract: Background: Mesenchymal stromal cells are a safe and promising option to treat knee osteoarthritis as previously demonstrated in different clinical trials. However, their efficacy, optimal dose and addition of adjuvants must be determined. Here, we evaluated the clinical effects of a dose of 100x106 bone marrow mesenchymal stromal cells (BM-MSCs) in combination with Platelet Rich Plasma (PRGF®) as adjuvant in a randomized clinical trial.Methods: A phase II, multicenter, randomized clinical trial with active co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The dMM-induced OA model in mice is an effective animal model first established in 2007 (21), whereby removing the medial meniscus can pathologically disrupt the stability status of normal knee joints, which can restrict the range of motion (52). Using the widely recognized dMM-induced model, the present study demonstrated the rescue effect of curcumenol in OA of the knee joint, as it effectively mitigated inflammation in the cartilage of the tibia and femur, as well as preventing joint space collapse and osteophyte formation.…”
Section: Discussionmentioning
confidence: 99%
“…The dMM-induced OA model in mice is an effective animal model first established in 2007 (21), whereby removing the medial meniscus can pathologically disrupt the stability status of normal knee joints, which can restrict the range of motion (52). Using the widely recognized dMM-induced model, the present study demonstrated the rescue effect of curcumenol in OA of the knee joint, as it effectively mitigated inflammation in the cartilage of the tibia and femur, as well as preventing joint space collapse and osteophyte formation.…”
Section: Discussionmentioning
confidence: 99%
“…In our search from the last year, we found 6 new reviews but only 3 new small RCTs (n ¼ 40, 47 and 60) comparing an injected stem cell therapy intervention against active control intervention 27e29 . Two of these studies 28,29 , in patients with knee and temporomandibular joint OA, estimated between-group differences in pain at 6 months or beyond. In both instances these differences were not statistically significant.…”
Section: Theme 6: Stem Cell Treatmentsmentioning
confidence: 99%
“…They demonstrated that subchondral MSCs had a significant effect on pain to postpone or avoid the TKA in the contralateral joint of patients with OA. In a phase II multicenter randomized controlled clinical trial, 60 OA patients received 10 × 10 7 cells of autologous BMSCs along with platelet-rich plasma and followed up for 12 months [119]. No serious adverse effects were observed after MSCs injection or during follow-up.…”
Section: Bone Regenerationmentioning
confidence: 99%